Middle-class projects in modern Malaysia. Issue 1 (2nd January 2017) - Fischer, Johan
Abstract : Within the last two decades or so there has been increased scholarly focus on the emergence, consolidation and future of the middle class in developing Asia. This is also the case with the Malay Muslim middle class in Malaysia, but how this class is developing over time is not well understood even if the Malays constitute the largest and fastest growing section of the middle class in Malaysia. Based on research projects I have carried out from the mid-1990s to the present, this article argues that an unpacking of the Malay Muslim middle class over time is important in order to understand the broader picture surrounding this class and its relationship to Malaysian national repertoires such as Islamic revivalism, politics, consumer culture, social mobility and the state-market nexus. I understand middle-class projects to be the making of local class culture in Malaysia and explore these in four research projects that each in their own way examine how Malay Muslim informants understand and practice "middle-classness" in different spatial and temporal contexts. In short, my findings show how Malay Muslim middle-class projects such as Islamic consumption shape local class culture in Malaysia.